Um projeto de unidade de ensino potencialmente significativa nas cores de Newton por meio dos fenômenos ópticos - Chagas, Placilene Cardoso das (2017)
In the present work the study of the colors of Newton is proposed by the basic knowledge of Geometric Optics For knowledge about colors, it is necessary to have a minimum of knowledge about the optical phenomena: reflection, refraction and absorption, since the type of visual perception, which hours can be understood as an artistic approach, can also be explained by other areas of knowledge, such as physics. There are few literatures in physics that discuss or mention the colors and explain how they are perceived by the eyes. The methodology of Teaching and learning that we use to make this approach is the meaningful learning of Ausubel, in which the construction of knowledge is guided by previous knowledge, which is the essence of this theory. The exposition of the organization of knowledge is done by conceptual maps and the degree of knowledge is verified by the taxonomy SOLO. The implementation of the proposal was carried out in a Public State School with two classes of second years, each with an average of 30 students per class, where their previous knowledge was verified, then executed the previous organizers. We elaborated a didactic sequence thinking about activities carried out by the teacher and the students, as well as the process of developing the project from the increasing problems situations to be solved by the students. Initially, the students answered the questions individually and then formed groups of students who developed a problem text and experimental activities, an integral part of the product of this work. The results obtained through the didactic sequence based on meaningful learning were the gradual development of knowledge in optics, specifically in Newton's colors.